2016
DOI: 10.7324/japs.2016.60222
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics: Knowledge, Attitude and Practice among Future Doctors and Pharmacists - A Pilot Study

Abstract: Rational application of genomics into practice would lead to safer chemotherapy through individualized medicine. The increasing trends of genetic discoveries coupled with increased adoption of pharmacogenomics in developed countries pose challenges to the presence and future healthcare professionals, not only in Malaysia. This research, aimed to assess knowledge, attitude and practice of final-year future healthcare professionals towards pharmacogenomics. A cross-sectional study was conducted by administering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…Consistent with other studies assessing the barriers and facilitators of PGx implementation [23,24,39,42,51], the lack of genomic education in medical and pharmacy programs and the lack of continuing education on PGx was addressed by the participants in this study. When performing a survey on medical and pharmacy students, Yau and Haque found that over 90% of pharmacy students have had a university class on PGx compared with 57% of medical students [57]. This finding suggests that pharmacy graduates may be better prepared than PCPs for the arrival of PGx in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies assessing the barriers and facilitators of PGx implementation [23,24,39,42,51], the lack of genomic education in medical and pharmacy programs and the lack of continuing education on PGx was addressed by the participants in this study. When performing a survey on medical and pharmacy students, Yau and Haque found that over 90% of pharmacy students have had a university class on PGx compared with 57% of medical students [57]. This finding suggests that pharmacy graduates may be better prepared than PCPs for the arrival of PGx in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The expectation among patients for prescribing physicians to be able to respond to PGx test results will have important implications for the broader implementation of PGx testing. A 2016 survey of pharmacy and medical students conducted by Yau and Haque [21] found that over 90% of pharmacy students had a course on PGx, while only 57% of medical students reported the same experience.…”
Section: Discussionmentioning
confidence: 99%
“…The completion of the Human Genome Project in 2003 along with the presentation of the Precision Medicine (now AllOfUs; https://allofus.nih.gov) initiative in 2015 (Mullard, 2015), boosted PGx recognition and therefore it became known for its potential applications and benefits in patient care, while other national-wide genomic medicine initiatives, such as the Genomics England are currently underway (reviewed in Patrinos et al, 2020). The implementation of PGx significantly contributes to the decrease of health care cost owing to several factors such as the drop of incidence of adverse drug reactions, the adjustment of drug dosing, the possibility of performing less unsuccessful clinical trials, and in shorten time, the adoption of a personalized therapeutic approach based on a patient genetic makeup (Yau and Haque, 2016;Klein et al, 2017). All these positive aspects drew public's attention and gained unexpected popularity in many countries such as the example of Singapore and the launch of a 10-years program of Precision Health Research (https://www.npm.sg), resulting in its wider application in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%